A new species of Buresilia (Opiliones, Phalangiidae) from Turkey - Kurt, Kemal; Kurt, Pinar (Zootaxa, 2024)
A new harvestman species, Buresilia gumushanensis sp. nov. (Opiliones: Phalangiidae), is described based on male specimens collected from Gümüşhane province, Turkey. Detailed descriptions, diagnostic features and pictures of the new species are provided, together with mitochondrial cytochrome c oxidase subunit I (COI) sequences. The phylogenetic tree constructed using the COI gene region revealed the phylogenetic position of the genus Buresilia within the family Phalangiidae. In addition, the new species is compared with known species of the genus Buresilia.